2018
DOI: 10.1139/gen-2017-0186
|View full text |Cite
|
Sign up to set email alerts
|

Genetic classification of Aegilops columnaris Zhuk. (2n=4x=28, UcUcXcXc) chromosomes based on FISH analysis and substitution patterns in common wheat × Ae. columnaris introgressive lines

Abstract: Aegilops columnaris is a tetraploid species originated from Ae. umbellulata (2n=2x=14, UU) and a yet unknown diploid grass species. Although Ae. columnaris possesses some agronomically valuable traits, such as heat and drought tolerance and resistance to pests, it has never been used in wheat breeding because of difficulties in producing hybrids and a lack of information on the relationships between Ae. columnaris and common wheat chromosomes. In this paper, we report the development of 57 wheat - Ae. columnar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…However, chromosome pairing is affected by diverse factors, and the reliability of failed chromosome pairing as an indicator of genome dissimilarity has been questioned 9 11 . Molecular cytogenetic methods such as C-banding, fluorescence in situ hybridization and genomic in situ hybridization have also helped to generate useful information on genome differences and phylogenetic relationships in the Triticeae 1 – 3 , 12 , 13 . Other molecular approaches, including isozyme analysis, variations in low-molecular-weight glutenin subunit and DNA marker systems have provided some explanations on Aegilops-Triticum relationships, the origin and differentiation of Aegilops species, and intra- and inter-specific variations in the D and U genome clusters of Aegilops species 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, chromosome pairing is affected by diverse factors, and the reliability of failed chromosome pairing as an indicator of genome dissimilarity has been questioned 9 11 . Molecular cytogenetic methods such as C-banding, fluorescence in situ hybridization and genomic in situ hybridization have also helped to generate useful information on genome differences and phylogenetic relationships in the Triticeae 1 – 3 , 12 , 13 . Other molecular approaches, including isozyme analysis, variations in low-molecular-weight glutenin subunit and DNA marker systems have provided some explanations on Aegilops-Triticum relationships, the origin and differentiation of Aegilops species, and intra- and inter-specific variations in the D and U genome clusters of Aegilops species 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the substitution of 6Ag i (6D) from Ag. intermedium was previously identified in the cultivars Favorit and Voevoda, while the Lebyodushka cultivar had the genes Sr6Ag i + Lr19/Sr25 (combination of substitution 6Ag i (6D) and translocation 7DS-7DL-7Ae#1L) (Sibikeev et al, 2017a), and the translocation 7DS-7DL-7Ae#1L from tall wheatgrass with gene Sr25/ Lr19 was identified in the Dobrynya cultivar (Badaeva et al, 2018). The presence of the gene Sr25 in the Dobrynya and Lebyodushka cultivars is confirmed in this work (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…neglecta [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], but the origin of these two species was a subject of long debates and is still not clear. Analysis of meiotic chromosome pairing in intraspecific hybrids [ 15 , 16 , 17 , 18 ], comparison of karyotype structure [ 19 ] and C-banding patterns [ 13 , 20 ], molecular analysis on nuclear [ 11 , 12 ] and cytoplasmic DNAs [ 21 , 22 ] showed that one of the Ae. columnaris and Ae.…”
Section: Introductionmentioning
confidence: 99%
“…comosa exhibited low chromosome pairing [ 15 ]. Differences in the patterns of variation of the repetitive nucleotide sequences [ 11 , 26 ], RAPD-spectra [ 9 ], the results of DArTseq-based analysis [ 12 ], comparison of karyotype structures [ 19 ], C-banding, and Fluorescence in situ hybridization (FISH)-patterns [ 13 , 20 ] contradicted this hypothesis. Taking into consideration the distinctness of Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation